2018
DOI: 10.1038/s41598-018-29015-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of characteristic scales of convection on non-isothermal evaporation of a thin liquid layer

Abstract: Here, the effect of convection in liquid on non-isothermal evaporation of a horizontal thin layer on a hot wall is investigated. It is considered that the evaporation rate of salts always decreases with the growth of salt concentration. Depending on the nature of evaporation rate, the aqueous salt solutions can be classified into two different types: (1) the equilibrium partial pressure of water vapor ps varies slightly with time; (2) with an increase in salt mass concentration, ps decreases many times, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Many works study the synthesis of gas hydrates under various conditions including the addition of promoters [10][11][12][13][14][15][16], as well as their dissociation, e.g., during combustion [17][18][19][20]. In this case, a very important aspect is the study of the thermal and convective processes [21,22]. A team of authors is currently developing several original methods for the synthesis of gas hydrates, which are based on the boiling of liquefied gas in a volume of water [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Many works study the synthesis of gas hydrates under various conditions including the addition of promoters [10][11][12][13][14][15][16], as well as their dissociation, e.g., during combustion [17][18][19][20]. In this case, a very important aspect is the study of the thermal and convective processes [21,22]. A team of authors is currently developing several original methods for the synthesis of gas hydrates, which are based on the boiling of liquefied gas in a volume of water [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that the synthesis process itself is nontrivial and complex, effective intensification of which requires taking a set of measures. There are many studies on synthesis of gas hydrates under various conditions [5][6][7][8][9][10][11][12]; it is important to analyze thermal and convective processes [13,14]. The process of gas hydrate decomposition is also complex; there are many respective studies, including those with combustion of the gas released during the dissociation of hydrate [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, one concludes that the effective solution to this challenge is to use a spray liquid cooling system [1]. Several heat transfer mechanisms are important for drop evaporation, namely, convection [2] and evaporation in the contact line. Previous studies showed an extremely high heat flux of 1,2 kW/cm 2 with water spray cooling, which is anticipated to be a key in solving thermal management problems of high-power electronic components because of its efficient heat removal.…”
Section: Introductionmentioning
confidence: 99%